DNA Methylation of Cannabinoid Receptor Interacting Protein 1 Promotes Pathogenesis of Intrahepatic Cholangiocarcinoma Through Suppressing Parkin‐Dependent Pyruvate Kinase M2 Ubiquitination. Issue 5 (25th March 2021) - Chen, Diyu; Wu, Hao; Feng, Xiaode; Chen, Yunhao; Lv, Zhen; Kota, Vishnu Goutham; Chen, Junru; Wu, Wenxuan; Lu, Yuejie; Liu, Hua; Zhang, Yanpeng; Zheng, Shusen; et al.
Abstract : Background and Aims: Methylation landscape is important for maintaining the silence of cannabinoid receptor–interacting protein 1 (CNRIP1) in some tumors. However, the role of CNRIP1 in intrahepatic cholangiocarcinoma (ICC) remains poorly defined. Approach and Results: In our study, we showed that CNRIP1 was down‐regulated in ICC tissues, and low expression of CNRIP1 was significantly associated with poor prognosis of patients with ICC in 3‐year overall survival and tumor‐free survival. Investigating the genomic DNA methylation profile, we disclosed a CpG island site named CNRIP1 MS‐2 (CNRIP1 methylation site‐2) that contributes to the down‐regulation of CNRIP1. In addition, the methylation level of CNRIP1 MS‐2 was correlated to the pathological grade, metastasis, and tumor–node–metastasis classification in ICC. Notably, we observed that CNRIP1 suppressed tumor cell migration, invasion, and proliferation by inhibiting the activity of pyruvate kinase M2 (PKM2). Sustained overexpression of CNRIP1 suppressed the in vivo tumor growth in a mouse xenograft model. It was also found that CNRIP1 overexpression activated Parkin (an E3 ubiquitin ligase), which resulted in the protein degradation of PKM2 in ICC cells. Conclusions: We identified that CNRIP1 acted as a putative tumor suppressor in ICC, which suggested that CNRIP1 could be a candidate biomarker for predicting tumor recurrence in patients with ICC. Furthermore, these findings highlight a potential therapeutic approach in targeting the CNRIP1/Parkin/PKM2 pathway for the treatment of ICC.